The validity and effectivity of learning using STEAM module with biotechnology game - Hilya Wildana Sofia; Anjar Putro Utomo; Slamet Hariyadi; Bevo Wahono; Erlia Narulita (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Provision of teaching materials in term of module can be an alternative to meet the learning needs of science. The study aimed at describing science module constructed based on Science, Technology, Engineering, Art and Mathematics (STEAM) equipped with valid and effective biotechnology games for learning science in junior high school. This Research and Development (R&D) was developed using the 4D model (Thiagarajan). This research was conducted at MTsN (State of Islamic Secondary School) 2 Jember, involved 30 IX graders. The design used was one group pretest-posttest design as the test of effectiveness. This study used STEAM-based science module equipped with biotechnology games, test, and validation sheets as research instruments. The validation results by experts were converted into categories. The effectivity test data was analyzed using N-gain and paired samples t-test. The average of validation results of material, media, and users was 87.17 (very valid). The effectivity test results showed the increase of students’ cognitive learning outcome [N-gain value = 0.72 (high category), t(29) = 9.030, p < 0.05]. Therefore, the module developed is valid and effective in improving the learning of biotechnology science which means that the use of this module is recommended to be implemented in biotechnology learning process.